POTRET PENDIDIKAN SEKS DALAM NOVEL NYAI GOWOK KARYA BUDI SARDJONO - Pradani, Tia; Rasiah, Rasiah; Supriatna, Agus (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2022)
The article tries to reveal the Javanese sex education portrayed in the novel Nyai Gowok written by Budi Sardjono. Nyai Gowok tells of a teenage boy named Bagus Ssasongko, the son of a highly respected Wedana in Randu Pitu, Central Java, in the 1950s. The newly circumcised boy is said to be entrusted to a guy to learn about sex and to realize himself as a auctioneer of the universe (a real man). Sociology of literature was used to describe the portraiture of sex education in the novel qualitatively. It is revealed that Nyai Gowok is depicting sex education through several point, the first, the sex educator through two figures of women; Nyai Lindri and Martinah, while the character to being educated is Bagus Sasongko. Gowok has duty to teach the boy boy starting from acquainting woman's body, from head to toe, from sensitive parts to the level of sex as well as another supporting items to extend the quality of sex; consuming Jamu, using mantra and tembang Jawa. An intimate relationship in Javanese philosophy is something that is sacred, noble, and at the same time has a function in maintaining life harmony.